Financing Efficiency and Its Effect to Lecturer Performance and Student Learning Outcomes on Private College - Nano Sukmana (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
This study is entitled to the efficiency of funding and its influence on the performance of Lecturers and Student Learning Outcomes. The focus of the study is on how the efficiency of funding affects the performance of Lecturers and Student Learning Outcomes. The research method used is quantitative, using statistical tests: Correlation Analysis, Regression, and Path Analysis. Both the lecturer's performance and student learning outcomes. This finding shows the importance of financing that is managed efficiently and protected from various types of waste, misuse, and violations of various stipulations. The results of this study are that the Efficiency of Financing significantly influences both the performance of lecturers and the results of student learning. This finding shows how important funding is managed efficiently and avoiding various types of waste, misuse, and violations of various stipulated provisions. Lecturer performance and student learning outcomes are strategic factors that can determine the level of institutional performance achievement of Private Universities that are studied clearly and reliably.